USE OF CLOUD TECHNOLOGIES IN EDUCATION (Conference Zone, 2022)
The article discusses the use of cloud technologies in education and gives examples of the use of cloud technologies in education. In education, cloud technologies allow for a wider use of forms and methods of teaching and have been found to be one of the modern ways to accelerate and optimize the learning process.